Stress and coping among unmarried pregnant university students in South Africa - Thandiwe Msipu Phiri; Patrick Nyamaruze; Olagoke Akintola (BMC, 2021)
Abstract Background The improvement of maternal and child health (MCH) outcomes is an important part of the sustainable development goals (SDGs). MCH remains an important issue globally as the SDGs have not yet been achieved in most countries. Young women in universities are likely to experience unintended pregnancy due to risky sexual behaviors in tertiary institutions which is characterized by lack of condom and/or contraceptive use and coercion. Pregnant young women in an academic environment are susceptible to stressors associated with unintended pregnancy and academic demands of universities. However, very little is known about the stress and coping among young people in tertiary institutions who get pregnant during the course of their studies and choose to keep the pregnancy. Methods Participants were purposively selected among pregnant students and those in the puerperal period at the time of the study. Semi-structured qualitative interviews were undertaken to explore the experiences of pregnancy and early motherhood, with particular focus on the various stressors experienced and possible coping strategies employed by students. The data were audio-recorded and transcribed verbatim, then analysed using thematic analysis. Results The findings show that pregnancy and early motherhood was an experience that came with a lot of stress emanating from fear of parents' reactions, academic pressure, financial constraints, relationship problems with male partners and experiences of social stigma. Participants used emotion-focused and problem-focused coping strategies to deal with the stressors confronting them during and after their pregnancy. Conclusion The experiences of pregnant students are multifaceted and generally characterised by financial crisis, academic challenges, shame, strenuous relationships and transitioning into a new identity. A multipronged approach to healthcare for pregnant students that focus on comprehensive antenatal services, health education, health promotion, psychosocial interventions including academic counselling will have positive outcomes for young mothers and their children.